2019
DOI: 10.1111/jbi.13620
|View full text |Cite
|
Sign up to set email alerts
|

Global biogeographic structuring of tropical shallow‐water brittle stars

Abstract: Aim Biogeographic barriers emerged in the tropical oceans as continental masses moved with plate tectonics, and as the tropics contracted to lower latitudes from the late Eocene. These barriers have shaped tropical marine biodiversity. We characterize large‐scale diversity patterns for tropical brittle stars and investigate the effect of biogeographic barriers on these in space and time. Location Shallow‐water (<200 m) tropical oceans. Taxon Tropical shallow‐water brittle stars (class Ophiuroidea). Methods We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 64 publications
3
9
1
Order By: Relevance
“…O. guttatum is an outgroup of O. appressum and O. hendleri . In the phylogeny of Bribiesca-Contreras et al 8 (which does not include O. hendleri ) , O. guttatum is an outgroup to a clade composed of O. squamosissimum and O. vansyoci , but the lower resolution of COI in our data did not provide support for the node joining it with O. squamosissimum . O. appressum and O. hendleri are another amphi-isthmian pair, but probably separated earlier than the completion of the Isthmus (see below).…”
Section: Resultscontrasting
confidence: 82%
See 2 more Smart Citations
“…O. guttatum is an outgroup of O. appressum and O. hendleri . In the phylogeny of Bribiesca-Contreras et al 8 (which does not include O. hendleri ) , O. guttatum is an outgroup to a clade composed of O. squamosissimum and O. vansyoci , but the lower resolution of COI in our data did not provide support for the node joining it with O. squamosissimum . O. appressum and O. hendleri are another amphi-isthmian pair, but probably separated earlier than the completion of the Isthmus (see below).…”
Section: Resultscontrasting
confidence: 82%
“…The common ancestor of O. holmesii and O. teres split from the common ancestor of O. phoenium and O. cinereum . That O. phoenium and O. cinereum are sister to each other was also shown by Bribiesca-Contreras et al 8 , based on sequence from1462 exons and from COI, and by Christodoulou et al 9 based on the same data, plus sequence from 28S. These studies did not sample O. holmesii but reported that O. peruanum , which we did not sample, is sister to O. teres .…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The effect of plate tectonics on biogeography is the foundation of vicariance biogeography and evident in phylogenetic patterns [43]. Our results confirm that continental fragmentation also has a direct effect on global provinciality.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, bioregionalisation provides an essential tool and spatially explicit framework for conservation planning (Crisp & Cook, 2013;Ladle & Whittaker, 2011;Morrone, 2009). Recently, significant progress has been made in the field of bioregionalisation by incorporating evolutionary information from phylogenetic trees (Bribiesca-Contreras et al, 2019;Daru et al, 2020;Ye et al, 2019), instead of solely emphasising the importance of endemic taxa (e.g. Takhtajan, 1978;Wu, 1979) or using taxonomic dissimilarity (e.g.…”
Section: Introductionmentioning
confidence: 99%